Characterization of two industrial gas hydrate inhibitors using the 3-in-1 technique (2017)
Gas hydrates are crystalline compounds, present in nature and considered dangerous if their formation takes place inside gas or oil exploitation pipelines. The 3-in-1 technique is used to characterize two different industrial hydrate inhibitors on morphology, kinetics and phase equilibria. A mass fraction of 0.1% is used to evaluate both inhibitors and the results are compared to the uninhibited system and other hydrate inhibitors. The technique shows reliability comparing results from previous experiments and consistent replicates for this work. Both gas hydrate inhibitors are classified as Kinetic Inhibitors with a slight thermodynamic promoter effect. ?Sandwich? theory is proposed according to the results obtained in contact angle measurement and aging tests. The selection of one of the inhibitors is made based on the performance and advantages for field applications